2006
DOI: 10.1042/bst0340791
|View full text |Cite
|
Sign up to set email alerts
|

Regulation by Per-Arnt-Sim (PAS) kinase of pancreatic duodenal homeobox-1 nuclear import in pancreatic β-cells

Abstract: The transcription factor PDX-1 (pancreatic duodenal homeobox-1) is required for normal pancreatic development and for the function of insulin-producing islet beta-cells in mammals. We have shown previously that glucose regulates insulin gene expression in part through the activation and translocation of PDX-1 from the nuclear periphery to the nucleoplasm. We have also found that PASK [PAS (Per-Arnt-Sim) kinase], a member of the nutrient-regulated family of protein kinases, is activated in response to glucose c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 13 publications
0
33
0
Order By: Relevance
“…In particular, the functional importance of glucose-stimulated PDX-1 phosphorylation is unclear. Although some studies reported a stimulatory effect of PDX-1 phosphorylation (9 -12), others have come to opposite conclusions (8,(13)(14)(15)(16). These discrepancies are partly due to the fact that specific phosphorylated residues are likely to have different functional effects.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…In particular, the functional importance of glucose-stimulated PDX-1 phosphorylation is unclear. Although some studies reported a stimulatory effect of PDX-1 phosphorylation (9 -12), others have come to opposite conclusions (8,(13)(14)(15)(16). These discrepancies are partly due to the fact that specific phosphorylated residues are likely to have different functional effects.…”
mentioning
confidence: 66%
“…Phosphorylation downstream of the mitogen-activated protein kinase p38 and phosphatidylinositol 3-kinase was shown to stimulate PDX-1 nuclear localization (4, 9) whereas phosphorylation on Ser 269 by homeodomain-interacting protein kinase 2 (HIPK2) has been shown to lead to nuclear exclusion (37). Phosphorylation of Thr 152 by PASK has also been reported (16), although whether this occurs in vivo remains to be demonstrated. In this study, we were not able to detect a significant effect of glucose on Thr phosphorylation of immunoprecipitated PDX-1 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…nuclear-cytoplasmic shuttling) or function would allow for acute alterations to target gene transcription, where control on the order of seconds to minutes might be crucial. At least 3 different reversible post-translational modifications, including phosphorylation [86,108,[110][111][112][113][114], sumoylation [115], and glycosylation [116], have been proposed to explain nuclearcytoplasmic shuttling and/or other functions of Pdx1. Consistent with these modifications, different molecular weight species of Pdx1 have been described in immunoblots [115].…”
Section: Mechanism Of Pdx1 Action Posttranslational Modifications Of mentioning
confidence: 99%
“…Of the three modifications, phosphorylation is perhaps the best-studied. Elevated glucose levels have been suggested to promote Pdx1 phosphorylation through one or a combination of several pathways, including the stress-activated protein kinase (SAPK) and extracellular signalregulated kinase (ERK) 1/2 pathways [86,108,112], phosphatidylinositol 3-kinase pathway [117,118], and/or the Per-Arnt-Sim (PAS) kinase [110]. Although the role of phosphorylation of specific residues within Pdx1 has not been rigorously analyzed, phosphorylation of Ser61 and Ser66 of Pdx1 via glycogen synthase kinase 3 appears to target Pdx1 for proteosomal degradation, thereby decreasing its half-life.…”
Section: Mechanism Of Pdx1 Action Posttranslational Modifications Of mentioning
confidence: 99%
“…In addition, a recent report suggested that PASKIN expression as well as kinase activity is increased in isolated pancreatic -cells following stimulation with high glucose levels [10]. Increased PASKIN activity appeared to be required for glucose-dependent transcriptional induction of preproinsulin gene expression, which might be related to PASKIN-dependent regulation of the nuclear import of pancreatic duodenal homeobox-1 transcription factor [11].…”
Section: Introductionmentioning
confidence: 99%